Effect of Magneto Priming on Seed Germination of Sesame (Sesamun indicum) Seed under Water Stress Conditions - M. Janalizadeh Ghazvini; A. Nezami; H.R. Khazaie; M. Goldani; H. Feizi (علوم و فناوری بذر ایران, 2017)
In order to investigate the effect of magneto priming on seed germination of sesame seed under water stress conditions, a factorial experiment based on a completely randomized design with three replications was carried out in 2014 in Ferdowsi University of Mashhad. Dry seeds of sesame exposed to magnetic fields (control (no priming), 25 mT[1] for 10 minutes and 75 mT for 60 minutes) bulky, then they treated by Polyethylene glycol 6000 (PEG6000) with different potentials (control (distilled water), -2, -4, -6 and -8 bar). Finally, germination traits such as germination percentage, germination rate, plumule and radicle length, dry weight of plumule and radicle and seedling length and seedling weight vigour indices were measured. The results showed that magneto priming led to increment of germination rate, radicle and plumule length, radicle dry weight and seedling length and seedling weight vigour indices, especially in high levels of water stress compared with control treatment. Radicle length of magneto primed sesame seeds with 75 mT (for 60 minutes) in -8 bar was 16.6% and radicle dry weight of magneto primed seeds with 25 mT (for 10 minutes) at the same level of water stress, was 64.4% more than control (no priming). In addition in -8 bar potential, due to priming with 75 and 25 mT intensities of magnetic fields, seedling length and weight vigour indices enhanced 38% and 22.6%, respectively, in comparison to control treatment. [1] mili Tesla